The Nixon Administration and the Middle East peace process, 1969-1973 : from the Rogers Plan to the outbreak of the Yom Kippur War - Vanetik, Boaz (Sussex Academic Press, 2013)
The Yom Kippur War was a watershed moment in Israeli society and a national trauma whose wounds have yet to heal some four decades later. In the years following the war many studies addressed the internal and international political background prior to the war, attempting to determine causes and steps by political players and parties in Israel, Egypt and the United States. But to date there has been no comprehensive study based on archival materials and other primary sources. Classified documents from that period have recently become available and it is now possible to examine in depth a crucial period in Middle East history generally and Israeli history in particular. The authors provide a penetrating and insightful viewpoint on the question that lies at the heart of the Israeli polity and military: Was an opportunity missed to prevent the outbreak of the Yom Kippur War? The book provides surprising answers to longstanding issues:? How did National Security Adviser, Henry Kissinger, succeed in torpedoing the efforts of the State Department to bring about an interim agreement between Israel and Egypt in 1971?? Would that agreement have allowed Israel to hold on to most of the Sinai Peninsula for many years and at the same time avert the outbreak of the war.? Did Golda Meir reject any diplomatic initiative that came up for discussion in the years preceding the war?? Was the White House's Middle East policy throughout 1973 a catalyst for war breaking out?